Response of dispersive cylindrical cloaks to a nonmonochromatic plane wave - Blanchard, Cédric (2012)
The transmission line modeling method is used to get the time domain response of a dispersive cylindrical cloak to an electromagnetic (EM) plane wave that is slightly nonmonochromatic. Our objective is to numerically study two important phenomena derived from the dispersive nature of the invisibility shell: frequency shifts and time delays. On one hand, the frequency domain representation of the cloak’s response shows that the frequency center is shifted once the EM wave has crossed the cloak; the shift intensity representation spans the entire rainbow spectrum depending on the observation angle. On the other hand, such a full-wave simulation constitutes tangible evidence of the existence of time delays when the EM wave passes through the device. We show that this phenomenon depends on the employed coordinate transformation.